Characterization of the electrical penetration graphs of the psyllid Bactericera trigonica on carrots. Issue 2 (18th April 2017) - Antolinez, C.A.; Moreno, A.; Appezzato‐da‐Gloria, B.; Fereres, A.
Abstract: The psyllid Bactericera trigonica Hodkinson (Hemiptera: Triozidae) is a carrot and celery pest recently described as a vector of the plant pathogenic bacterium Candidatus Liberibacter solanacearum (Lso) on Apiaceae. Detailed information on vector stylet penetration activities is essential in the study of Lso transmission. In this study we used the electrical penetration graph (EPG) technique, characterized waveforms produced during the various stylet penetration activities in carrot leaves, and correlated them with stylet tracks and salivary sheath termini on plant tissues as well as with Lso inoculation. In addition, the effect of Lso in B. trigonica on the stylet penetration activities was tested. The EPG waveforms identified were: waveforms C1 and C2 detected in the mesophyll, waveforms D, E1, and E2 near or in the phloem sieve elements, and waveform G in the xylem vessels. A waveform pattern not previously reported for psyllids was the 'pseudo‐potential drop' (pseudo‐pd), characterized by sudden voltage dips similar to potential drops. However, the lowered voltage appeared to be inverted when the plant voltage is negative, indicating that it is caused by an increased resistance period and not due to a cell puncture. A direct correlation is shown between the waveform E1 and salivation into phloem sieve elements by B. trigonica as the inoculation of Lso occurred in a period as short as 30 s of E1; Lso transmission occurred in 17 of 35 plants (48%). Stylet activities during waveforms C or D had no consequences on the inoculation of Lso. In conclusion, Lso infection directly affects the probing behaviour of B. trigonica by increasing the total duration of C and D waveforms, but not variables related to phloem salivation (Lso inoculation) or ingestion (Lso acquisition). The reported information here is fundamental for identifying the psyllid vector traits of behaviour associated with transmission of Lso to Apiaceae.